Induction of reproduction of fish Anasa Nomorhampus sp. endemic Palu, Central Sulawesi orally through hormon bioencapsulation use Chironomus sp. - Dinda Wahyu Rezki; Agus Oman Sudrajat; Dinar Tri Soelistyowati; Odang Carman (Jurnal Akuakultur Indonesia, 2025)
Species Nomorhampus sp. with the local name Anasa fish, endemic to Palu, Central Sulawesi, has a unique superior mouth shape, beak-shaped jaws, attractive colors and patterns, becoming an export commodity with high economic value, but currently it cannot be cultivated, domestication efforts are needed to avoid extinction, by carrying out hormonal manipulation that accelerates the domestication process. This study aims to evaluate the effectiveness of Oodev® on the induction of reproduction in the fish Nomorhampus sp. through bioencapsulation using Chironomus sp. which resulted in births, five groups of fish were fed using Oodev® at a dose of 1 mL/kg parent weight and NaCl 1 mL/kg parent weight as a control group, the fish were kept for 60 days. This research focuses on assessing specific weight growth rate (LPBS), specific length growth rate (LPPS), survival rate (TKH), gonadosomatic index (IGS), gonadal histology, birth frequency, number of births, and growth performance. Fish fed Oodev® feed showed higher SGR and IGS (p<0.05), 40% of fish fed Oodev® supplementary feed successfully gave birth with a total of 9 fry, while no birth occurred in control fish. Histological analysis showed faster gonad development in fish fed Oodev®. Hormonal induction with Oodev® can accelerate reproduction in anasa fish in cultivation containers. These findings provide valuable insight for fish farmers regarding the effect of Oodev® on gonad development in anasa fish in both male and female parents. It is hoped that this discovery will speed up the process of domestication of Anasa fish.